Physical Activity Over the Life Course and its Association with Cognitive Performance and Impairment in Old Age - Middleton, Laura E (2010)
OBJECTIVE: To determine how physical activity at various ages over the life course is associated with cognitive impairment in late life. DESIGN: Cross-sectional study SETTING: Four US sites. PARTICIPANTS: We administered a modified Mini-Mental State Examination (mMMSE) to 9344 women ≥65 years (mean 71.6 years) who self-reported teenage, age 30, age 50, and late life physical activity. MEASUREMENTS: We used logistic regressions to determine the association between physical activity status at each age and likelihood of cognitive impairment (mMMSE score >1.5SD below the mean, mMMSE≤22). Models were adjusted for age, education, marital status, diabetes, hypertension, depressive symptoms, smoking, and body mass index. RESULTS: Women who reported being physically active had lower prevalence of cognitive impairment in late life compared to women who were inactive at each time (teenage: 8.5% vs. 16.7%; adjusted Odds Ratio (95% Confidence Interval): 0.65 (0.53–0.80); age 30: 8.9% vs. 12.0%; 0.80 (0.67–0.96); age 50: 8.5% vs. 13.1%; 0.71 (0.59–0.85); old age: 8.2% vs. 15.9%; 0.74 (0.61–0.91)). When the four times were analyzed together, teenage physical activity was most strongly associated with lower odds of late-life cognitive impairment (OR=0.73 (0.58–0.92)). However, women who were physically inactive at teenage and became active in later life had lower risk than those who remained inactive. CONCLUSIONS: Women who reported being physically active at any point over the life course, and especially at teenage, have lower likelihood of cognitive impairment in late life. Interventions should promote physical activity early in life and throughout the life course.